Cardiovascular disease and air pollution in Scotland: no association or insufficient data and study design? - Willocks Lorna J; Bhaskar Abita; Ramsay Colin N; Lee Duncan; Brewster David H; Fischbacher Colin M; Chalmers James; Morris George; Scott E (BMC, 2012)
Abstract Background Coronary heart disease and stroke are leading causes of mortality and ill health in Scotland, and clear associations have been found in previous studies between air pollution and cardiovascular disease. This study aimed to use routinely available data to examine whether there is any evidence of an association between short-term exposure to particulate matter (measured as PM10, particles less than 10 micrograms per cubic metre) and hospital admissions due to cardiovascular disease, in the two largest cities in Scotland during the years 2000 to 2006. Methods The study utilised an ecological time series design, and the analysis was based on overdispersed Poisson log-linear models. Results No consistent associations were found between PM10 concentrations and cardiovascular hospital admissions in either of the cities studied, as all of the estimated relative risks were close to one, and all but one of the associated 95% confidence intervals contained the null risk of one. Conclusions This study suggests that in small cities, where air quality is relatively good, then either PM10 concentrations have no effect on cardiovascular ill health, or that the routinely available data and the corresponding study design are not sufficient to detect an association.